El derecho a la defensa en la obtención de los elementos de prueba dentro del proceso penal. - Garofalo Pilamunga, Henry Ismael (2024)
The present work is aimed at identifying those forms of defenselessness that presumably originate in some cases where the prosecution does not provide elements of evidence or elements of conviction when by right the procedural subjects request greater support for their theories, especially the defendant. , in such a way that you also have the guarantee of fully demanding a legitimate right of defense; That is why the so-called investigation aims to recognize in some cases prosecutorial actions in a way that presumptively and indicatively affects the right to defense. For these purposes, from a mixed, cross-sectional approach, when used on bibliographic data of information regarding the right to defense, the elements of evidence and other legal characteristics will allow us to achieve one of the first expected products: grouping the knowledge that can contribute to the work to make evident the violation of the defendant's right to defense where in certain proceedings that are unknown, the prosecutor's office does not fully complete the operation of delivering elements of conviction when required by the aforementioned procedural subject; Through the survey and interview we were allowed to obtain conclusions and recommendations. Curricular Integration Project that starts from considering that with the promulgation of the new Comprehensive Organic Criminal Code, the criminal guarantee seeks to control the punitive power of the state against citizens with judicial efficiency, thinking about the rights of the accused and the victims, observing the implementation of institutions aimed first at the ordinary procedure which in turn is divided into 3 stages, one of them is the tax instruction, which among several of its purposes seeks to obtain the necessary elements of conviction for the procedural parties to so that they can defend themselves, and that is where it originates that the core body of the criminal process, which is the prosecutor's office, manages to fail to comply with the requests already dispatched in relation to carrying out the corresponding actions with the objective of granting elements of evidence, to this end that harms the subjects of the criminal dispute. 5 Keywords: Criminal procedure, Prosecuted, Procedural subject, Right to defense, Elements of Conviction, Elements of proof, Evidence.